2019
DOI: 10.1093/mnras/stz1220
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the QSO contribution to the 21-cm signal from the Cosmic Dawn

Abstract: The upcoming radio interferometer Square Kilometre Array (SKA) is expected to directly detect the redshifted 21-cm signal from the neutral hydrogen present during the Cosmic Dawn. Temperature fluctuations from X-ray heating of the neutral intergalactic medium can dominate the fluctuations in the 21-cm signal from this time. This heating depends on the abundance, clustering, and properties of the X-ray sources present, which remain highly uncertain. We present a suite of three new large-volume, 349 Mpc a side, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
45
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 114 publications
(169 reference statements)
6
45
1
Order By: Relevance
“…The upper limits from Mertens et al (2020) at scales k = 0.075 and 0.1 h Mpc −1 are ∆ 2 = (58.97) 2 mK 2 and (95.21) 2 mK 2 respectively (see also Table 1). Before proceeding, it should be realized that these values are rather high compared to the power spectrum at redshift ≈ 9.1 predicted by various standard reionization scenarios, such as in Mellema et al (2006a), Iliev et al (2007), Greig & Mesinger (2015), Ghara et al (2015b), Hassan et al (2016), Bolgar et al (2018) and Ross et al (2019). For example, the predicted power spectra at z ≈ 9 at k = 0.1 h Mpc −1 are found to be 10 3 mK 2 .…”
Section: Modelling the 21-cm Signal Using Grizzlymentioning
confidence: 88%
“…The upper limits from Mertens et al (2020) at scales k = 0.075 and 0.1 h Mpc −1 are ∆ 2 = (58.97) 2 mK 2 and (95.21) 2 mK 2 respectively (see also Table 1). Before proceeding, it should be realized that these values are rather high compared to the power spectrum at redshift ≈ 9.1 predicted by various standard reionization scenarios, such as in Mellema et al (2006a), Iliev et al (2007), Greig & Mesinger (2015), Ghara et al (2015b), Hassan et al (2016), Bolgar et al (2018) and Ross et al (2019). For example, the predicted power spectra at z ≈ 9 at k = 0.1 h Mpc −1 are found to be 10 3 mK 2 .…”
Section: Modelling the 21-cm Signal Using Grizzlymentioning
confidence: 88%
“…Refs. [50,51] showed that spin temperature fluctuations can have a strong impact on non-Gaussianity of the signal. Ref.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The strength of the redshifted 21-cm signal from the CD depends on the gas temperature and background Lyα flux which are determined by the radiation sources and the heating/cooling processes. Several heating processes such as X-ray heating (Pritchard & Furlanetto 2007;Mesinger et al 2013;Ghara et al 2015bGhara et al , 2016Ross et al 2019;Islam et al 2019), shock heating (Furlanetto & Loeb 2004) and heating due to resonance scattering of Lyα photons (hereafter 'Lyα heating') (Chen & Miralda-Escudé 2004;Chuzhoy & Shapiro 2007;Furlanetto & Pritchard 2006) can increase the kinetic temperature of the gas in the IGM during these epochs. However, the relative contribution of these mechanisms is uncertain.…”
Section: Introductionmentioning
confidence: 99%